2019
DOI: 10.3390/healthcare7010042
|View full text |Cite
|
Sign up to set email alerts
|

An Increasing Neutrophil-to-Lymphocyte Ratio Trajectory Predicts Organ Failure in Critically-Ill Male Trauma Patients. An Exploratory Study

Abstract: Background: Although the association of neutrophil proportions with mortality in trauma patients has recently been shown, there is a paucity of research on the association with other outcomes. We sought to investigate the association of neutrophil proportions with organ failure in critically-ill trauma patients. Methods: We reviewed a randomly-selected group of trauma patients admitted to our level-1 trauma intensive care unit between July 2007 and December 2016. Data collected included demographics, injury me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…6B and D). The neutrophil–lymphocyte ratio (NLR) has been recently recognized as an independent prognostic indicator of systemic inflammation 18 and organ failure 19 . This ratio was found elevated upon lewisite exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6B and D). The neutrophil–lymphocyte ratio (NLR) has been recently recognized as an independent prognostic indicator of systemic inflammation 18 and organ failure 19 . This ratio was found elevated upon lewisite exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have evaluated the association between NLR and outcomes in multi-trauma patients, demonstrating worse outcomes with increasing NLR. A recent study had found that a trajectory of increasing NLR over the first 48 h of admission is associated with the development of organ failure among male trauma patients [10]. Another study realizes that NLR is strongly associated with early mortality in trauma patients with severe hemorrhage managed with multi-transfusion protocol (MTP) [11].…”
Section: Discussionmentioning
confidence: 99%
“…High serum levels of IL-8 and over-expression of its receptor (CXCR2) on the neutrophils in patients with severe trauma have been reported, which correlate with neutrophil hyperactivity and poor prognosis (178,181). Moreover, high levels of NLR (>5.27) over 24 to 48 hours post-trauma are significantly correlated with early MOF (182) and mortality (183). Hence, the level of CD11b and CXCR2, as well as NLR at the time of admission, may be valuable predictors to identify the inflammatory state and risk of mortality in trauma patients.…”
Section: Neutrophilmentioning
confidence: 99%